The Effect of the Quantum Teaching Model on Student Learning Outcomes in IPAS Subjects in Grade IV of SDN 155712 Tumba Jae 2 - Simbolon, Riskianmo; Tanjung, Darinda Sofia; Juliana; Silaban, Patri Janson; Purba, Frikson Jony; Ann John, Jeena (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The research aims to analyze the effect of the Quantum Teaching model. The results show that the average learning outcome of IPAS in grade IV is 82.13, which is categorized as good. Of the 30 students studied, 24 students (84%) met the Minimum Passing Criteria (KKTP), while 4 students (16%) did not meet the KKTP. This study is a quantitative study that aims to determine the effect of the Quantum Teaching model on student learning outcomes in IPAS in grade IV at SD Negeri 155712 Tumba Jae 2. The population was all 30 students in grade IV. The sample was taken based on the total sampling technique, namely 30 students. Student learning outcomes showed that the average pre-test score for fourth-grade students was 54.8, while the post-test score was 82.13. The results of this study indicate that the learning outcomes of IPAS students using the Quantum Teaching learning model are in the strong category with a correlation coefficient of 0.902, which means that rcount 0,902 ≥ rtable 0.36), so Ha is accepted. Furthermore, hypothesis testing shows that tcount is 11.077, while ttable is 2.048, proving that the hypothesis is greater than ttable, so Ho is rejected and Ha is accepted. Thus, it can be concluded that the Quantum Teaching model (X) has a positive and significant effect on learning outcomes (Y). This indicates that the Quantum Teaching learning model has an effect on students' IPAS learning outcomes. Thus, all questionnaire instruments in this study are declared reliable and trustworthy, as they have met the minimum requirements specified.